A systematic review on lagged associations in climate–health studies. (15th January 2021) - Wang, Pin; Zhang, Xuyi; Hashizume, Masahiro; Goggins, William B; Luo, Chao
Abstract: Background: Lagged associations in climate–health studies have already been ubiquitously acknowledged in recent years. Despite extensive time-series models having proposed accounting for lags, few studies have addressed the question of maximum-lag specification, which could induce considerable deviations of effect estimates. Methods: We searched the PubMed and Scopus electronic databases for existing climate–health literature in the English language with a time-series or case-crossover study design published during 2000–2019 to summarize the statistical methodologies and reported lags of associations between climate variables and 14 common causes of morbidity and mortality. We also aggregated the results of the included studies by country and climate zone. Results: The associations between infectious-disease outcomes and temperatures were found to be lagged for ∼1–2 weeks for influenza, 3–6 weeks for diarrhoea, 7–12 weeks for malaria and 6–16 weeks for dengue fever. Meanwhile, the associations between both cardiovascular and respiratory diseases and hot temperatures lasted for <5 days, whereas the associations between cardiovascular diseases and cold temperatures were observed to be 10–20 days. In addition, rainfall showed a 4- to 10-week lagged association with infectious diarrheal diseases, whereas the association could be further delayed to 8–12 weeks for vector-borne diseases. Conclusion: Our findings indicated some general patterns for possible lagged associations between some common health outcomes and climatic exposures, and suggested a necessity for a biologically plausible and reasonable definition of the effect lag in the modelling practices for future environmental epidemiological studies.